The Renaissance of the Sanskrit Language: An Imperative for Modern Times - Chhetri, Bishnu Silwal (Journal of Business and Social Sciences, 2024)
Sanskrit labelled as the "language of Divine," boasts a distinctive place in the linguistic and cultural legacy of the globe. Its profound influence on Eastern philosophy, science, literature, languages, and religion emphasizes its historical significance. However, Sanskrit confronts apathy and marginalization in the modern world. The present research explores the various motives behind the resurgence of Sanskrit, emphasizing its relevance in the contemporary world through language analysis, technical usage, and rejuvenation of culture. Overall, this study argues for a deliberate and worldwide resurrection of Sanskrit in order to harness its potential for modern society and possible future advancements by examining its historical origin, current challenges, and prospective possibilities.